2010
DOI: 10.1089/jwh.2009.1362
|View full text |Cite
|
Sign up to set email alerts
|

Carraguard® Acceptability Among Men and Women in a Couples Study in Thailand

Abstract: Men and women in this study found the gel acceptable and thought that it should be made available if it is found to be safe and effective. Strategies for marketing a potential microbicide product must take the target population into consideration. For married couples, key considerations may be partner dynamics and trust issues, whereas messages focusing on sexual pleasure or disease prevention may resonate more strongly with sex workers or other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Additionally, analysis of data from highly adherent participants in the Carraguard (PC-515, 3% CG) Phase 3 trial suggested that CG decreases HPV acquisition (Marais et al, 2011). These data, combined with the excellent safety profile of CG (Crostarosa et al, 2009; Kilmarx et al, 2008; Kilmarx et al, 2006; Martin et al, 2010; Skoler-Karpoff et al, 2008; Turville et al, 2008; Whitehead et al, 2006), have supported clinical testing of PC-515 and Divine 9 gel to prevent HPV. Here we compare the physicochemical properties of both gels, examining their in vitro and in vivo efficacy against different HPV types.…”
Section: Introductionmentioning
confidence: 81%
“…Additionally, analysis of data from highly adherent participants in the Carraguard (PC-515, 3% CG) Phase 3 trial suggested that CG decreases HPV acquisition (Marais et al, 2011). These data, combined with the excellent safety profile of CG (Crostarosa et al, 2009; Kilmarx et al, 2008; Kilmarx et al, 2006; Martin et al, 2010; Skoler-Karpoff et al, 2008; Turville et al, 2008; Whitehead et al, 2006), have supported clinical testing of PC-515 and Divine 9 gel to prevent HPV. Here we compare the physicochemical properties of both gels, examining their in vitro and in vivo efficacy against different HPV types.…”
Section: Introductionmentioning
confidence: 81%
“…CG represents an excellent delivery vehicle for ZA. It has been shown to be safe and acceptable in numerous preclinical and clinical studies (7,19,22,(25)(26)(27)(28)(29)(30)(31)(32) despite contradictory observations using in vitro systems that CG can enhance HIV infection (22,33). Additionally, CG may have activity against HPV (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Carrageenan gel is an appealing delivery vehicle for rectal microbicides because it has been shown to be safe and acceptable for vaginal use in humans (10,27,28,33,35,45,54), safe when applied to the rectal epithelia of mice (49), and both safe and acceptable rectally in a small human trial (41). Carrageenan also has favorable rheological properties for delivering antiretroviral drugs (12,50).…”
Section: Discussionmentioning
confidence: 99%
“…While Carraguard, a 3% carrageenan gel, was found not to be effective in significantly reducing the number of HIV infections in the treatment arm compared to placebo in a phase 3 clinical trial (45), it was shown to be safe and acceptable by the women who used it in the trial (45) as well as by participants in other studies (27,28,33,35,41,54). Carrageenan-based gels also have favorable rheological properties (12,50), rendering them promising candidates for delivering potent antiviral agents.…”
mentioning
confidence: 99%